2005
DOI: 10.2139/ssrn.843024
|View full text |Cite
|
Sign up to set email alerts
|

Robbing the Riches: Capital Flight, Institutions, and Instability

Abstract: This Working Paper should not be reported as representing the views of the IMF.The views expressed in this Working Paper are those of the author(s) and do not necessarily represent those of the IMF or IMF policy. Working Papers describe research in progress by the author(s) and are published to elicit comments and to further debate.Capital flight may undermine economic growth and the effectiveness of debt relief and foreign aid. This paper is the first attempt to test whether unsound macroeconomic policies or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…Consequently, mass exodus of capital will be recorded over time, meaning lost and missing domestic savings-investments. This finding, which supports that of Cuddington (1987), Nyoni (2000), Harrigan et al (2002), Felding (2003 and Cerra et al (2005), also brings to mind the Asian financial crisis of the late 1990's and the massive Capital Flight that followed the monumental exchange rate depreciation of the region. By implication, maintaining suitable balance of payment position, which helps sustain stable exchange rate is a good way to prevent Capital Flight.…”
Section: Discussionsupporting
confidence: 82%
“…Consequently, mass exodus of capital will be recorded over time, meaning lost and missing domestic savings-investments. This finding, which supports that of Cuddington (1987), Nyoni (2000), Harrigan et al (2002), Felding (2003 and Cerra et al (2005), also brings to mind the Asian financial crisis of the late 1990's and the massive Capital Flight that followed the monumental exchange rate depreciation of the region. By implication, maintaining suitable balance of payment position, which helps sustain stable exchange rate is a good way to prevent Capital Flight.…”
Section: Discussionsupporting
confidence: 82%
“…Capital flight estimates for Trinidad and Tobago were previously calculated using the Residual or Broad Estimate of capital flight adjusted for Trade Misinvoicing and inflation for the period, 1971-2011. This commonly used measure is supported by several economists including Ajilore (2010), Cerra et al (2005), Henry (1996), Schneider (2000) and Vukenkeng and Mukete (2016) and calculated as shown by the equations below:…”
Section: Datamentioning
confidence: 99%
“…As Rodriguez (1987, p. 136) noted: "When capital flight is financed by external borrowing, the negative consequences multiply". In most cases, external loans are not used to finance investment or consumption, but to finance capital flight itself, implying a mutually reinforcing bi-directional relationship between debt and IFFs (the so called 'revolving door' syndrome) (Rodriguez 1987;Chipalkatti and Rishi 2001;Boyce 2003, 2011;Boyce and Ndikumana 2005;Cerra et al 2005;Beja 2007;Ndikumana et al 2015). Moreover, the need to pay off this debt and the debt service limits governmental ability to increase spending on the health sector or other social sectors.…”
Section: Iffs and Human Developmentmentioning
confidence: 99%
“…In this regard, Ndikumana and Boyce (2011) suggested that each additional dollar allocated to debt servicing means 29 cents less allocated to public health spending. In addition, Cerra et al (2005) found that debt accumulation fuels subsequent capital flight more strongly in countries with weak institutions and high income inequality. Moreover, the prospect of capital flight has led many governments to adopt a conservative fiscal policy stance, which has limited revenue and resulted in public expenditure cuts, especially in social and infrastructure sectors (Stiglitz 2000).…”
Section: Iffs and Human Developmentmentioning
confidence: 99%